2018
DOI: 10.1002/mp.12852
|View full text |Cite
|
Sign up to set email alerts
|

Application of statistical and computational methodology to predict brainstem dosimetry for trigeminal neuralgia stereotactic radiosurgery

Abstract: For the first time, an advanced statistical and computational methodology was applied to study the impact of anatomical and technical variables on TN SRS. The variables were found to impact brainstem doses, and reasonably strong correlation models were established using an optimized 3-feature combination including the nerve incidence angle, cone size, and isocenter-brainstem distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Increasing the dose to the brainstem seems to be related to a better pain control and a higher rate of trigeminal dysfunction [20]. Higher dose to the brainstem may result either from targeting a more proximal portion of the nerve, from a shorter nerve length, or both, which results in a higher exposure of the sensory bers [19,22,34]. The best nerve portion to target remains controversial: most authors suggest that more proximal targets induce more hypesthesia but better pain control [4,18,19,22], whereas some others did not nd any relation between position of the target and outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the dose to the brainstem seems to be related to a better pain control and a higher rate of trigeminal dysfunction [20]. Higher dose to the brainstem may result either from targeting a more proximal portion of the nerve, from a shorter nerve length, or both, which results in a higher exposure of the sensory bers [19,22,34]. The best nerve portion to target remains controversial: most authors suggest that more proximal targets induce more hypesthesia but better pain control [4,18,19,22], whereas some others did not nd any relation between position of the target and outcome [26].…”
Section: Discussionmentioning
confidence: 99%
“…This negative correlation between hypoesthesia and treatment success has previously been described [ 11 ] and may be explained by technical considerations. Indeed, it has been demonstrated that the outcome of TN radiosurgery was influenced by interdependent technical parameters such as total dose to the target, shot size, length of treated nerve, dose delivered to the brainstem, location of the target within the nerve and volume of the proximal nerve irradiated [ 6 , 13 , 21 26 , 30 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…When MRI cannot be performed on a patient, a CT cisternogram is needed, which requires the contrast agent injection into the cerebrospinal fluid (CSF) via a spinal tap. 238,244 The radiation oncologists contour the OARs, including the brainstem, cochlea, ipsilateral facial nerve (CN7), auditory vestibular nerve (CN8), ipsilateral temporal lobe, as well as the target. The length of CN5 selected as the target is somewhat arbitrary, so once delivery errors are taken into consideration, portions of the prescribed isodose volume could fall outside of the target but still overlap with CN5.…”
Section: Methodsmentioning
confidence: 99%
“…Using this technique, one can safely deliver 50 to 60 Gy in a single fraction to a 4 to 10 mm length of nerve typically about three millimetres wide. 238 Studies by Romanelli et al 239,240 and Villavicencio et al 241 have reported on the efficacy of CyberKnife SRS for the treatment of trigeminal neuralgia. Villavicencio et al 241 reported a preliminary multi-center study in which 67% of patients (N = 95) experienced initial pain relief, and 50% continued pain relief in a two-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation